Longitudinal impact of early childhood science instruction on 5th grade science achievement. Issue 7 (2nd May 2020) - Kaderavek, Joan N.; Paprzycki, Peter; Czerniak, Charlene M.; Hapgood, Susanna; Mentzer, Gale; Molitor, Scott; Mendenhall, Robert
ABSTRACT: This study investigated if student placement in a primary grade 1–3 classroom with a teacher who had been trained in a U.S. science Framework-aligned [National Research Council. (2012). A framework for K-12 science education: Practices, crosscutting concepts and core ideas . The National Academies Press] professional development science approach impacted student science achievement as measured in 5th grade. Students in the treatment group also received take-home science materials and treatment families were invited to participate in community-based science events. A two-level, random-slope mixed regression model was used to assess the effect of the treatment on later student achievement as measured by performance on the Science Subtest of the Ohio Achievement Assessment. This study found that students from the treatment group scored significantly higher on 5th grade science tests as compared to their peers. Overall, this study suggests that providing Framework-aligned science instruction, coupled with parent support, during early years improves science skills in later elementary grades.